Trends and policy implications of the location selection of electric and electronic firms in Malaysia: a case study of the Penang and Kulim High-Tech Parks - Fauziah Che Leh (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Space has great impact on an economy organisation as it influences many other significant matters including the location selection aspect. Hence, it is crucial to observe the location aspect in order to look into the industrial activities as well as the development in a geography space. Clearly, not only the location aspect will affect the manufacturing industry operation ineffectiveness, but will also disturb the production process and similarly affect the competency among the firms. Furthermore, the location problem will appear to be a threat to location attraction force in order to attract the foreign investors who will eventually develop the manufacturing industry sectors. This study examined the criteria considered by the electric and electronic industrial firms in Penang and Kulim Hi-Tech Park industrial areas. Primary data were gathered from surveys and interviews of firms chief executives, manufacturing department director, R&D department manager, engineer, human resource department manager and other relevant officers directly involved in the decision making process of 30 electric and electronic industrial firms in Penang and another 10 in Kulim Hi-Tech Park. Findings from the survey showed that government policies, education infrastructure, research, and the environment were among the main criteria influencing the location decision of the firms studied. These criteria proved to be no different from those employed by industrial firms in developed countries.